Effect of Lubrication Environments on Wear Performance of Ball Bearing Materials - Amiruddin, Hilmi; Abdollah, Mohd Fadzli bin; Mazlan, Mohd Afiq Azfar; tamaldin, noreffendy (2014)
From the past researches, wear of materials are effectively reduced by different gas lubrications. However, researches on this topic are not much explored. Thus, in this study, the wear performance of a ball bearing material sliding in air with O2- or N2-gas blows were investigated using a systematic approach, which is Taguchi method.